2014
DOI: 10.1016/j.jbankfin.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of: The impact of enterprise risk management on the marginal cost of reducing risk: Evidence from the insurance industry

Abstract: a b s t r a c tWe test the hypothesis that practicing enterprise risk management (ERM) reduces firms' cost of reducing risk. Adoption of ERM represents a radical paradigm shift from the traditional method of managing risks individually to managing risks collectively allowing ERM-adopting firms to better recognize natural hedges, prioritize hedging activities towards the risks that contribute most to the total risk of the firm, and optimize the evaluation and selection of available hedging instruments. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 45 publications
6
57
0
2
Order By: Relevance
“…In response to unexpected threats, one school of thought believed in the direct impact of ERM on firm performance (Callahan and Soileau 2017;Florio and Leoni 2017;Zou and Hassan 2017) while another group of researchers claimed that the relationship of ERM and firm performance could be affected by some internal factors (Khan and Ali 2017;Wang et al 2010). Much research has discussed the importance of ERM practices among businesses (Eckles et al 2014;Florio and Leoni 2017;Yilmaz and Flouris 2017). In fact, most of the studies have been conducted particularly in developed economies (Florio and Leoni 2017) while SMEs in emerging economies have received comparatively limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…In response to unexpected threats, one school of thought believed in the direct impact of ERM on firm performance (Callahan and Soileau 2017;Florio and Leoni 2017;Zou and Hassan 2017) while another group of researchers claimed that the relationship of ERM and firm performance could be affected by some internal factors (Khan and Ali 2017;Wang et al 2010). Much research has discussed the importance of ERM practices among businesses (Eckles et al 2014;Florio and Leoni 2017;Yilmaz and Flouris 2017). In fact, most of the studies have been conducted particularly in developed economies (Florio and Leoni 2017) while SMEs in emerging economies have received comparatively limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling for such characteristics, they found that higher ERM quality is associated with improved accounting performance. Eckles et al (2014) found that insurance companies with ERM experience a reduction in stock return volatility and that operating profi ts per unit of risk (ROA/return volatility) increase after ERM adoption, indicating a positive effect of ERM on the company's performance. The only study suggesting that ERM does not infl uence a company's value is McShane et al (2011).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…To determine whether a company uses ERM we followed the methodology used by Gordon et al (2009), Hoyt andLiebenberg (2011), and Eckles et al (2014). We performed a thorough search of companies' SEC fi lings for every company in the sample and analyzed in detail sections of fi lings where keywords related to ERM appeared.…”
Section: Variables' Measurementmentioning
confidence: 99%
See 2 more Smart Citations